Application of ReOx/TiO2 catalysts with excellent SO2 tolerance for the selective catalytic reduction of NOx by NH3. Issue 15 (30th June 2021) - Yu, Yanke; Yi, Xianfang; Zhang, Jiali; Tong, Zhaojian; Chen, Changwei; Ma, Mudi; He, Chi; Wang, Jinxiu; Chen, Jinsheng; Chen, Bingbing
Abstract : The adsorption of SO2 on ReO x /TiO2 catalysts was rather weak; thus, ReO x /TiO2 catalysts exhibited excellent SO2 tolerance in the NH3 -SCR reaction. Abstract : Non-vanadium-based catalysts with high SO2 tolerance are still interesting in selective catalytic reduction of NO by NH3 (NH3 -SCR) and SO2 adsorption is the foremost step for the deactivation of catalysts. In order to alleviate the adsorption of SO2, we fabricated a series of rhenium (Re; without stable sulfate) supported TiO2 catalysts and studied their SO2 tolerance for the first time. Owing to suitable surface acidity and reducibility, ReO x /TiO2 catalysts exhibited satisfactory activity in a wide temperature range of 250–350 °C. As expected, experimental results and DFT calculations indicated that SO2 adsorption on ReO x /TiO2 catalysts was rather weak, thus the catalysts performed excellent SO2 tolerance in the NH3 -SCR reaction. Moreover, in situ DRIFTS indicated that the NH3 -SCR reaction on ReO x /TiO2 catalysts followed the Eley–Rideal mechanism and SO2 had little effect on the reaction mechanism. Our findings should provide new insights into the development of SCR catalysts with high SO2 tolerance.